Concordance of Immune-Related Markers in Lymphocytes and Prefrontal Cortex in Schizophrenia. Issue 1 (6th February 2021) - Gatta, Eleonora; Saudagar, Vikram; Drnevich, Jenny; Forrest, Marc P; Auta, James; Clark, Lindsay V; Sershen, Henry; Smith, Robert C; Grayson, Dennis R; Davis, John M; Guidotti, Alessandro
Abstract: Schizophrenia is a severe neuropsychiatric disorder associated with a wide array of transcriptomic and neurobiochemical changes. Genome-wide transcriptomic profiling conducted in postmortem brain have provided novel insights into the pathophysiology of this disorder, and identified biological processes including immune/inflammatory-related responses, metabolic, endocrine, and synaptic function. However, few studies have investigated whether similar changes are present in peripheral tissue. Here, we used RNA-sequencing to characterize transcriptomic profiles of lymphocytes in 18 nonpsychotic controls and 19 individuals with schizophrenia. We identified 2819 differentially expressed transcripts ( P nominal < .05) in the schizophrenia group when compared to controls. Bioinformatic analyses conducted on a subset of 293 genes ( P nominal < .01 and |log2 FC| > 0.5) highlighted immune/inflammatory responses as key biological processes in our dataset. Differentially expressed genes in lymphocytes were highly enriched in gene expression profiles associated with cortex layer 5a and immune cells. Thus, we investigated whether the changes in transcripts levels observed in lymphocytes could also be detected in the prefrontal cortex (PFC, BA10) in a second replication cohort of schizophrenia subjects. Remarkably, mRNA levels detected in the PFC and lymphocytes were in strong agreement, and measurements obtained using RNA-sequencing positively correlated with data obtained by reverse transcriptase-quantitative polymerase chain reaction analysis. Collectively, our work supports a role for immune dysfunction in the pathogenesis of schizophrenia and suggests that peripheral markers can be used as accessible surrogates to investigate putative central nervous system disruptions.